Oral Health Awareness, Practices and Status of Patients with Diabetes attending a Tertiary Health Institution in Nigeria (2016)
Despite the reported increasing prevalence of diabetes mellitus, very few studies have documented report on oral health awareness and oral health conditions of individuals with diabetes mellitus from our environment. Thus this study aimed at assessing the oral health awareness, practices and status of individuals with diabetes mellitus attending a tertiary health facility in Nigeria. A cross sectional survey of 143 patients with diabetes attending the medical outpatients' clinic of the hospital. Information was obtained from participants using pretested structured questionnaires and oral examination. Tests of associations were determined using Chi-square and student t test. One-fifth (20.3%) of the respondents were aware of good oral health preventing oral diseases in diabetes. Thirty-five (24.5%) knew that diabetes could worsen oral health condition and only 3 (2.1%) could correctly explain the association between diabetes and oral health conditions. Forty-three (30.1%) had participated in an oral health education program focused on diabetes and oral health. The majority (88.6%) had calculus accumulation while none had a healthy periodontium. Oral health awareness, practices and status of patients with diabetes were poor in our environment. Thus, these individuals need to be better informed of the relationship between oral health and diabetes